Advocate Legal Education in Indonesia: The Need of Spiritual Dimensions Approach - Agiyanto, Ucuk; Absori, Absori; Surbakti, Natangsa; Raharjo, Trisno; Ikhwan, Afiful (Al-Risalah, 2021)
Law No. 18 of 2003 explains that someone who wants to be an advocate must take advocate professional education. This professional education is based on the enforcement of justice and pursues to strengthen the Rule of Law principles. This study offers the importance of spirituality in advocate education, in order to create an officium nobile who puts justice for the marginal community over the injustice rules. This research method uses a non-doctrinal qualitative approach based on law implementation in society, combined with a philosophical system related to spirituality that integrates science and religion. This study concludes that advocate education with a spiritual dimension is an effort to uphold the advocate profession as an official representative, prioritizing justice access in the community rather than profit, especially in bribery or corruption.